Sociopreneurship Sebagai Tren Karir Anak Muda - Hempri Suyatna; Yanti Nurhasanah (Universitas Gadjah Mada, 2017)
The Demographic Bonus that has taken place in this decade has a significant influence on Indonesia's social, political, economic and cultural system. Youth who are the drivers of the demographic bonus are rapidly taking up positions and roles in the world of workforce to the political and idealism platforms that intersect on the space of capitalism. In taking on the role of the flow of economic system, several youth feel that they have the potential and space of freedom to develop business and self potential through the way of entrepreneurship. Furthermore, youth are trying to take the role of becoming a social entrepreneur agent. Socioenterpreneurship is not new for several youth as the key to reducing the level of disparities in Indonesia. In addition, the emergence of smart city trends, a challenge the government to collaborate with the private sector and civil society to create a good social business ecosystem in the village. In other hand, smart village becomes an interesting output as the mainstreaming goal of sociopreneurship. Empowerment and creative economy become a play area for youth and society to do social business. Especially with the potential of nature and international market share has been from history always looking at the creative products of young Indonesians. So, this is not difficult to achieve. This paper is a partial summary of the results of the author's experience in interacting for several years with start-ups, creative economy business actors, social business communities, and social entrepreneurs in the community. From the results of this paper, it was found that youth with a variety of technologies that are very fast and sophisticated have begun to looking social business opportunities as a choice of survival amid their narrowness in finding a job. Social entrepreneurship becomes one of the keys for the Indonesian state to accelerate rapid and equitable economic and social development.